Deceptively yours: Valence-based creativity and deception. (March 2017) - Kapoor, Hansika; Khan, Azizuddin
Highlights: Positive and negative creativity were assessed using real-world divergent thinking tasks. Deception was differentially related to positive and negative creativity. Trait deception was associated with both valences of creativity. The process of deception was used to reach a creative outcome only in negative creativity. Results suggest that implicitly valenced processes, like deception, can interact with the cognitive process of creativity. Abstract: Recent research has been investigating positive and negative valences of creativity; that is, using the creative process to meet positive and/or negative goals set by respective stakeholders. Given the past association between creativity and deception, this study examined whether deception was differentially related to these valences of creativity. Participants ( N = 169) completed a real-world divergent thinking task, and responded to measures of trait deception and ideational fluency. Responses were coded for originality, valence, and whether deception was used to address the situation. Results supported the overall relationship between trait deception and originality. In the high creative subsample ( n = 42), trait deception predicted not just originality, but also both valences of creativity. However, in contrast to positive creativity, individuals were more likely to use deceptive and creative processes only to engage in negative creativity. Thus, deception as a process variable was associated with negative creativity. In the four Ps framework of creativity (Rhodes, 1961), results suggested that deception operated as a Person component in positive creativity, but as Person and Process facets in negative creativity. Implications for future research include identifying other cognitive processes along which the valences of creativity differ, and assessing such differences via electrophysiological means.